2018
DOI: 10.2478/pjen-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal effect of essential oil and powder of Mentha pulegium L. leaves against Sitophilus oryzae (Linnaeus, 1763) and Tribolium castaneum (Herbst, 1797) (Coleoptera: Curculionidae, Tenebrionidae), the main pests of stored wheat in Morocco

Abstract: Stored grains are threatened by several insects, leading to losses in quality and quantity. Several studies have revealed the risks of using chemicals that can cause serious health problems for humans. It is in this perspective that the objective of our work should be seen: It was to assess the effect of the essential oil and leaf powder of Mentha pulegium against Sitophilus oryzae and Tribolium castaneum adults attacking post-harvest cereals. The insecticidal activity of the essential oil against these two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Miguel et al [55] reported that M. pulegium induced 100% mortality to Ceratitis capitata (Diptera: Tephritidae) with 0.3% (w/v) EO in mucilage at 72 h after treatment. Similarly, M. pulegium oil exhibited greater toxicity (100%) against Sitophilus oryzae (Coleoptera: Curculionidae) and Tribolium castaneum (Coleoptera: Tenebrionidae) adults with 0.16 µL/cm 2 at 24 h [56] . In addition, several studies have also reported the toxicity of M. pulegium against various insects such as Hessian fly Mayetiola destructor (Diptera: Cecidomyiidae) [57], Bactrocera oleae (Diptera: Tephritidae) [41], Bemisia tabaci (Hemiptera: Aleyrodidae) [58], Camptomyia corticalis (Diptera: Cecidomyiidae) [59], Sitophilus zeamais (Coleoptera: Curculionidae) [60], and Helicoverpa armigera (Lepidoptera: Noctuidae) [61].…”
Section: Discussionmentioning
confidence: 99%
“…Miguel et al [55] reported that M. pulegium induced 100% mortality to Ceratitis capitata (Diptera: Tephritidae) with 0.3% (w/v) EO in mucilage at 72 h after treatment. Similarly, M. pulegium oil exhibited greater toxicity (100%) against Sitophilus oryzae (Coleoptera: Curculionidae) and Tribolium castaneum (Coleoptera: Tenebrionidae) adults with 0.16 µL/cm 2 at 24 h [56] . In addition, several studies have also reported the toxicity of M. pulegium against various insects such as Hessian fly Mayetiola destructor (Diptera: Cecidomyiidae) [57], Bactrocera oleae (Diptera: Tephritidae) [41], Bemisia tabaci (Hemiptera: Aleyrodidae) [58], Camptomyia corticalis (Diptera: Cecidomyiidae) [59], Sitophilus zeamais (Coleoptera: Curculionidae) [60], and Helicoverpa armigera (Lepidoptera: Noctuidae) [61].…”
Section: Discussionmentioning
confidence: 99%
“…verified that T. castaneum tolerated ozone gas better than S. zeamais . Lougraimzi et al 52 . affirmed that T. castaneum was more tolerant to pennyroyal essential oil ( Mentha pulegium L.) applied by fumigation than S. oryzae .…”
Section: Discussionmentioning
confidence: 99%
“…Scan time and mass range were 1 s and 50-550 m/z, respectively. Mass spectra (compared with Wiley Registry 9th Edition/NIST 2011 edition mass spectral library), comparison of their retention indices (RI) with either those in the literature [10] or with those of authentic compounds available in our laboratories were taken into account for the compound identification.…”
Section: Extraction and Analysis Of Volatile Compounds Retained By Th...mentioning
confidence: 99%
“…Lougraimzi et al, [9] highlighted that EO and leaf powder of Pennyroyal exhibited insecticidal activity against T. castaneum. In addition, Amoura et al [10] demonstrated a fumigant toxicity on T. confusum with an LC50 of 92.89 µL/L air. Then, M. piperita EO provided 50% of larval fumigant toxicity and 74 % of repellency of T. castaneum [11].…”
Section: Introductionmentioning
confidence: 99%